1997
DOI: 10.1086/304865
|View full text |Cite
|
Sign up to set email alerts
|

Where Do the Disks of Spiral Galaxies End?

Abstract: In spiral galaxies, the HI surface density declines with increasing radius to a point where it is seen to truncate dramatically in the best observed cases. It was anticipated that if the ambient radiation field is sufficiently strong, there exists a maximum radius beyond which the cold gas is unable to support itself against ionization. We have now succeeded in detecting ionized gas beyond the observed HI disk in spirals. Here, we report on our findings for the Sculptor galaxy NGC 253. The HI disks in Sculptor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
139
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(150 citation statements)
references
References 92 publications
(83 reference statements)
10
139
1
Order By: Relevance
“…Fig 3), but that reflects the fact that we have azimuthally averaged over 2π radians, as opposed to splitting into twelve π/6 segments and aligning at the "break"; as such, the lopsidedness "smears" the break in Fig 4 from 19 kpc to a range of radii spanning 19−26 kpc. The ionised disk extends ∼30−50% beyond the neutral disk, before being "lost" in the background corona, similar to that observed (Bland-Hawthorn et al 1997). Neutral and ionised gas density distributions for the "no polytrope" simulation of Ramses1.…”
Section: Gas Diskssupporting
confidence: 73%
“…Fig 3), but that reflects the fact that we have azimuthally averaged over 2π radians, as opposed to splitting into twelve π/6 segments and aligning at the "break"; as such, the lopsidedness "smears" the break in Fig 4 from 19 kpc to a range of radii spanning 19−26 kpc. The ionised disk extends ∼30−50% beyond the neutral disk, before being "lost" in the background corona, similar to that observed (Bland-Hawthorn et al 1997). Neutral and ionised gas density distributions for the "no polytrope" simulation of Ramses1.…”
Section: Gas Diskssupporting
confidence: 73%
“…The Galaxy's Eating Habits 409 the typical radius quoted for our Galaxy (~26 kpc), however it is possible that an extended ionized disk exists (e.g., Savage et al 2003), as found in other systems (Bland-Hawthorn, Freeman & Quinn 1997). The passage through an extended disk of our Galaxy, in addition to the tidal forces already obviously at work as evident from the stellar tidal stream, might have been enough to disrupt the HI in the core of the galaxy and cause the dwarf to lose all remaining star formation fuel.…”
Section: Discussionmentioning
confidence: 68%
“…Better statistics in this range of N H i could pin down a global value of the edge column density N 1/2 or find evidence for variations in N 1/2 (see the discussion in Corbelli & Bandiera 2002). The value of N 1/2 may well vary from place to place, because the flux of ionizing radiation may vary for two reasons: (1) more than 37% of directions on the sky have N H i above 1:6 Â 10 17 atoms cm À2 (unit UV optical depth at the Lyman edge; Murphy et al 1995), so the extragalactic flux may be highly obscured in some places and less so in others; and (2) in some galaxy group environments, the extragalactic ionizing UV flux may be greatly enhanced by some UV leaking out of galaxies (Bland-Hawthorn, Freeman, & Quinn 1997;Castellanos, Díaz, & Tenorio-Tagle 2002;Ciardi, Bianchi, & Ferrara 2002).…”
Section: Confinement Clumpiness and Other Uncertaintiesmentioning
confidence: 99%